Sliding Mode Control System of Single Phase Buck-Boost Inverter with Buffer Inductor - Purwadi Agus Darwito; Arief Abdurrakhman; Almas Fachrullah (IPTEK Journal of Proceedings Series, 2015)
Inverter is one of the primary components of a distributed electric power plants that serve as modifiers DC voltage into AC. In this research is applied of the Sliding Mode Control on Inverter Buck Boost One phase with Buffer Inductor. In the Open Loop test with the source voltage of 60 Volts, generate graphics output voltage in the form of a sinusoidal wave with maximum amplitude of about 400 volts. In the Closed Loop test, the graph output voltage can be controlled to follow a set point with SMC control method of order 2, and the resulting value Error Steady State smallest at 300 Volt, which amounted to 3.33%. The smallest sensitivity value of 0.29 when the input voltage changes by 32%.